Global Halal Market and Economic Development in Muslim Countries: A Systematic Literature Review from the Perspective of Maqashid al-Shariah - Ahmad Luthfi; Jimmi Saputra (Rangkiang: Journal of Islamic Economics and Business, 2026)
This study aims to synthesize the existing literature on the global halal market and analyze its contribution to the economic development of Muslim countries from the perspective of maq??id al-shar?‘ah. The study employs a Systematic Literature Review (SLR) approach based on the PRISMA 2020 framework. Literature was collected from the Scopus and Web of Science databases covering publications from 2019 to 2024. From an initial set of 52 articles, 20 studies met the inclusion criteria and were analyzed using thematic synthesis. The findings identify four dominant themes: global halal market expansion, halal supply chain development, the contribution of the halal industry to economic development, and the integration of halal governance with Islamic finance. The results suggest that the halal industry has the potential to enhance export competitiveness, strengthen small and medium enterprises (SMEs), create employment opportunities, and support sustainable economic development in Muslim countries. However, several challenges remain, including fragmented halal certification systems, regulatory inconsistencies, limited technological capabilities, and weak integration between halal industries and Islamic financial institutions. This study contributes theoretically by integrating halal economy literature with the framework of maq??id al-shar?‘ah and offers a conceptual foundation for developing a more inclusive, competitive, and sustainable halal ecosystem in Muslim countries.